UV-Vis diffuse reflectance spectra of vanadium-based catalysts: Potentialities of the praying Mantis diffuse reflectance accessory - Jeništová, Klára; Smoláková, Lucie; Čapek, Libor (University of Pardubice, 2015)
The aim of work is to study the vanadium-oxo species at V-alumina and V-silica catalysts by using of praying Mantis diffuse reflectance accessory, which enables to measure the spectra under reaction conditions. Firstly, we had focused on the elimination of setting problems with the praying Mantis diffuse reflectance accessory. Secondly, we analysed the distribution of vanadium-oxo species at Vsilica and V-alumina catalysts under oxygen atmosphere and under C2-ODH reaction conditions. It has been observed that the degree of vanadium polymerisation was higher on V-alumina in comparison to V-silica. The degree of polymerisation decreased at V-alumina and V-silica materials under presence of C2-ODH reaction conditions in comparison to the oxygen atmosphere.